Analysis Of Land Value Zone Due To Land Use Change For Kendal Special Economic Zone (Case Study: Kaliwungu Sub-District, Kendal Regency) - Fauzi Janu Amarrohman; Shofiyatul Qoyimah; Erlinda Nofianti (Journal of Applied Geospatial Information, 2025)
Land use change in Kaliwungu Sub-district due to the development of Kendal Special Economic Zone is significant. The method used in this processing is overlay method. The analysis method used to determine the influence of Kendal Special Economic Zone on Land Value Zone is linear regression analysis.  There was a significant land use change in 2015-2019 amounting to 937.29 hectares while in 2019-2023 amounting to 495.92 hectares used as Kendal Special Economic Zone. The change of land value zone in Kaliwungu Sub-district is quite significant in 2015-2019 with the biggest increase of IDR 2,896,000 while in 2019-2023 there is the biggest increase of IDR 9,674,000. Based on the results of the linear regression test, there is an influence of the independent variable distance with the dependent variable, namely NIR 2023, which is indicated by the R Square value of 0.075 or 7.5% of the influence. According to the correlation test between the independent variable of the distance of Kendal Special Economic Zone to the centroid zone to NIR 2023, there is no correlation between the two because the correlation value is 0.00, while the independent variable of the distance of the national road to the centroid zone to NIR 2023 has a correlation with a negative correlation value (-0.271), which means that the farther the zone is from the national road, the lower the land price will be.